Malaysian legal system: an introduction - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2014)
This chapter provides an overview of the Malaysian legal system how it evolved and why it changed with reference to the Malaysian legal history.Further, the chapter provides a summary content of the chapters.